Production of lignocellulolytic enzymes by Aspergillus niger biofilms at variable water activities - Villena, Gretty K.; Gutiérrez-Correa, Marcel (Electronic Journal of Biotechnology, 2007)
Lignocellulolytic enzyme production by Aspergillus niger was compared both in submerged fermentation (SF) and biofilm fermentation (BF) at varying water activities. Maximal filter paper activity, endoglucanase and xylanase activities were much higher in BF (2.96, 4.7 and 4.61 IU ml-1, respectively) than in SF cultures (1.71, 1.31 and 2.3 IU ml-1, respectively) but biomass yields were lower in BF than in SF (0.338 g g-1 and 0.431 g g-1, respectively). In the presence of 20% ethylene glycol (aw = 0.942) the enzyme activities decreased in both systems but BF still had higher levels (1.0, 1.0 and 2.6 IU ml-1, respectively) than SF cultures (0.6, 0.7 and 1.5 IU ml-1, respectively). An increase in xylanase specific activity of more than 2 fold (from 4.2 to 10.2 IU mg-1 biomass) was observed in the presence of 20% ethylene glycol, suggesting differential regulatory mechanisms in biofilm fermentation related to cell adhesion.